2018
DOI: 10.1371/journal.pone.0189493
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography with compressed sensing: An evaluation of moyamoya disease

Abstract: Compressed sensing (CS) reconstructions of under-sampled measurements generate missing data based on assumptions of image sparsity. Non-contrast time-of-flight MR angiography (TOF-MRA) is a good candidate for CS based acceleration, as MRA images feature bright trees of sparse vessels over a well-suppressed anatomical background signal. A short scan time derived from CS is beneficial for patients of moyamoya disease (MMD) because of the frequency of MR scans. The purpose of this study was to investigate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 32 publications
3
51
1
1
Order By: Relevance
“…From our results, CS techniques also can reduce the SENSE ghost artifacts, highlight the blood signal in the blood vessel, and suppress the background signal. Similar findings have been found in previous studies that the image quality of CS‐MRA is higher than MRA which only using a parallel imaging technique, with more than an acceleration factor of 3 . CS‐MRA scan was successfully performed in all enrolled patients without any technical problems in our study, which demonstrated its good feasibility and stability, consistent with a previous study …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…From our results, CS techniques also can reduce the SENSE ghost artifacts, highlight the blood signal in the blood vessel, and suppress the background signal. Similar findings have been found in previous studies that the image quality of CS‐MRA is higher than MRA which only using a parallel imaging technique, with more than an acceleration factor of 3 . CS‐MRA scan was successfully performed in all enrolled patients without any technical problems in our study, which demonstrated its good feasibility and stability, consistent with a previous study …”
Section: Discussionsupporting
confidence: 92%
“…In addition, CS‐MRA could reduce the scanning time through reconstruction with sparse undersampling of k ‐space data by exploiting image redundancies. In our study, the mean acquisition time of CS‐MRA was 2 minutes and 54 seconds, whereas Con‐MRA took 5 minutes and 49 seconds, the same as a previous study where the scanning time of CS‐MRA was 2 minutes and 42 seconds with an acceleration factor of 5 . The scanning time of Con‐MRA (nearly 6 min) is slightly longer for patients throughout the MRA scan, especially for patients with severe brain disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Hybrid CS was effective in high-contrast areas, so it was applied to MRA, the cine-image sequences of cardiac MRI, and MRCP. 8,12,16 The contrast and SNR of CSF for hybrid-CS were significantly higher compared with those for SENSE. However, contrast and SNR of muscle and fat for hybrid-CS were significantly lower compared with those for SENSE.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports mainly evaluated the usefulness of CS technique for reducing the scan time preserving image quality in sparse data such as magnetic resonance choledochopancreatography (MRCP) and brain MR angiography. 11,12 However, most MR images are not sparse in generalmost of the pixels in an MR image are not black, but contain many levels of the grayscale. Therefore, CS is not widely used for routine examinations.…”
Section: D Mri Can Bementioning
confidence: 99%